2016
DOI: 10.1246/bcsj.20160265
|View full text |Cite
|
Sign up to set email alerts
|

Bithiophene with Winding Vine-shaped Molecular Asymmetry. Preparation, Structural Characterization, and Enantioselective Synthesis

Abstract: Preparation of 2,2¤-bithiophene derivatives bearing ω-alkenyl groups at the 3,3¤-positions and ring-closing metathesis reactions of the obtained compound were performed. The reaction of bithiophene bearing 3-butenyl substituents 1 with 5 mol % Grubbs 1st generation catalyst underwent ring-closing metathesis (RCM) to afford the cyclized product 7 showing winding vine-shaped molecular asymmetry in up to 88% yield. Enantioselective RCM was also achieved by the use of chiral Schrock Hoveyda molybdenum-alkylidene c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…The angle was similar to that of the bithiophene derivative 2 (76.9°). [6] The CÀ C bond of the ethylenediamine moiety (C7-C8) was revealed to be intersected with the CÀ C bond between two benzene rings of biphenyl (C15-C16) with the torsion angle of 61.9°. By contrast, the aniline derivative 8 a' was found to show almost parallel conformation of the CÀ C bond of the two phenyl rings of biphenyl (C13-C14) and the CÀ C bond of the diamine moiety (C21-C22) with the torsion angle of 7.8°, as shown in Figure 2b.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The angle was similar to that of the bithiophene derivative 2 (76.9°). [6] The CÀ C bond of the ethylenediamine moiety (C7-C8) was revealed to be intersected with the CÀ C bond between two benzene rings of biphenyl (C15-C16) with the torsion angle of 61.9°. By contrast, the aniline derivative 8 a' was found to show almost parallel conformation of the CÀ C bond of the two phenyl rings of biphenyl (C13-C14) and the CÀ C bond of the diamine moiety (C21-C22) with the torsion angle of 7.8°, as shown in Figure 2b.…”
Section: Resultsmentioning
confidence: 99%
“…[5] It was also revealed that the obtained product exhibited molecular asymmetry, in which axial, helical, and planar chiralities were involved in the molecule and their inversion of the chirality took place in a synchronized manner. Separation of the enantiomer with HPLC on chiral stationary phase, [3,6] resolution with the preparative column, [3] and enantioselective metathesis [7,8] have been successful to afford the enantiomerically pure/enriched compounds. It was also shown to undergo an additional protocol to afford winding vine-shaped molecules employing annulative nucleophilic substitution with nosyl (2-nitrobenzenesulfonyl) diamines to give vine-shaped biaryl 2.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unsymmetrical heterbiaryls (±)- 4b , (±)- 4c , and (±)- 4e were prepared by the procedures in our previous report 22 . Bithiophene (±)- 4d was prepared by the procedure described in our previous report 21 . Racemic epoxides 3 and 5d were prepared by epoxidation of (±)- 1 and (±)- 4d with m -chloroperbenzoic acid or oxone/acetone in a manner described previously 23 .…”
Section: Methodsmentioning
confidence: 99%